A Prospective Study on the Relationship between Sports Injuries and some of the Physical Fitness Factors in Soccer Players - hassan, daneshmandi; Soheil, Haghshenas (Journal of Physical Education Health and Sport, 2018)
The purpose of this research was to study was the relationship between some of the physical fitness factors and sport injuries in soccer players. 69 senior soccer players (age: 22.83±3.06 yrs.), experienced (9.45±4.56 yrs.), that play in Guilan league participated in this study. Demographic information and sport activity were collected by questionnaire and interviews. Then muscle strength by manual muscle test, flexibility by sit reach test and aerobic power by Bruce test were assessed. Hawkinz and Fuller questioner with validity of 87% was used for collecting information about risk factors. Correlation coefficient and chi square test were used to analyze data (p≤0.05). The results showed that most injuries were in lower extremity (63.8) and muscular tissue (62.3). Also significant relationship was found between hip flexors strength (p=0.042), trunk flexors strength (p=0.044), trunk extensors strength (p=0.047), flexibility (p=0.022) and aerobic power (p=0.029) with injury. But was no significant relationship between hip extensors strength with injury. There is also significant relationship between experience, dominant leg, non-dominant leg and injury rate (p≤0.05). However was no significant relationship between age with injury rate. With respect to relationship between strength, flexibility and aerobic power (in fact physical fitness) with injury, seems that coaches and players should pay more attention to factors such as strength, aerobic power and flexibility. Also skill and experience of players should be   considered carefully.